Boosting Photothermal Theranostics via TICT and Molecular Motions for Photohyperthermia Therapy of Muscle‐Invasive Bladder Cancer (Adv. Healthcare Mater. 24/2021). Issue 24 (22nd December 2021) - Zeng, Sheng; Gao, Heqi; Li, Chuang; Xing, Shaoqiang; Xu, Zhaoliang; Liu, Qian; Feng, Guangxue; Ding, Dan
Abstract : Photothermal Therapies In article number 2101063 by Qian Liu, Guangxue Feng, Dan Ding, and co‐workers, a small photothermal molecule with active intramolecular motions and a dark state twisted intramolecular charge transfer feature is designed to boost the photothermal conversion ability. Such a design strategy enables the effective low‐temperature photo‐hyperthermia treatment of muscle‐invasive bladder cancers at low drug and laser dosages with minimal side effects.